The Role of Islamic Personality on Entrepreneurial Intention through Entrepreneurial Self-Efficacy - Assyofa, Allya Roosallyn; Maharani, Nina; Rohandi, Moch. Malik Akbar; Handri (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
Islam encourages Muslims to become entrepreneurs, where Islam encourage Muslims to become an entrepreneur, where entrepreneurs play an important role in economic growth and increasing employment opportunities. Students are prepared by universities to create jobs by providing entrepreneurship education. A personality that reflects Islamic traits can play an important role in increasing one's entrepreneurial self-efficacy. This study seeks to find the relationship between Islamic personality in forming entrepreneurial self-efficacy, which in turn influences students' intentions to engage in entrepreneurial activities. The respondents in this research were 195 students in Bandung. The data in this study were analysed using regression, correlation and path analysis. Verification data analysis is used to verify the truth of the hypothesis using SmartPLS 4.0. The results of this research show that Islamic personality has a significant positive effect on entrepreneurial intentions through entrepreneurial self-efficacy, apart from that entrepreneurial self-efficacy has the greatest influence on entrepreneurial intentions.